COMPLEMENT-FIXATION TITERS IN EXPERIMENTAL COCCIDIOIDOMYCOSIS IN RABBITS - Brosbe, Edwin A. (1964)
Brosbe, Edwin A. (Veterans Administration Hospital, Long Beach, Calif.), Jewell N. Kietzman, and Nathaniel B. Kurnick. Complement-fixation titers in experimental coccidioidomycosis. J. Bacteriol. 88:233–241. 1964.—The course of experimental coccicioidomycosis in rabbits was followed with complement-fixation (CF) tests. Uniformity of complement-fixing antibody response to large infective doses was observed, and levels as high as 1:4,096 in the New Zealand albino and 1:16,384 in the Dutch rabbit were attained. Mortality reflected the size of the inoculum rather than the level of CF titer. Animals receiving additional challenges displayed no marked elevation in titer, although high titers persisted. Nitrogen mustard, for the most part, did not influence the CF titer.